Planning and saving for retirement - Tomasz Sulka (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
Planning for retirement and subsequent execution of the plan are difficult, but essential for financial security in old age. To formally analyse the interplay between planning and self-control, I introduce cognitive costs of formulating a plan into the dual-self model of impulse control. The resulting model can generate rational inaction in pension choices, with the agent's self-control and level of income playing a role of inputs into the decision whether or not to undertake costly planning. Furthermore, when they do plan, agents characterised by poor self-control save over shorter horizons and accumulate lower pension wealth. The possibility of rational inaction can explain other robustly observed behaviours, such as disproportionately low savings of individuals on low incomes and non-fungibility between public and private pension wealth. The model is applied to study welfare and savings implications of automatic enrolment into private pensions. The default option effect on plan participation arises due to the fact that counterfactual non-savers have the lowest threshold for accepting the default scheme. Nevertheless, the impact of automatic enrolment on total savings is ambiguous in general, because in addition to the counterfactual non-savers, the default may anchor contributions of a counterfactual active saver to a low default contribution rate. Consequently, although raising the default contribution rate itself has an ambiguous impact on aggregate savings, it always reduces the dispersion in pension wealth accumulation.
Keywords: D14; D15; D91; E21; E71; H55; J32; 330; Planning; Self-Control; Cognitive Costs; Pensions; Automatic Enrolment